New Horizons in Radioligand Therapy: 161Tb-PSMA-617 in Advanced mCRPC. (8th May 2023) - Rosar, Florian; Maus, Stephan; Schaefer-Schuler, Andrea; Burgard, Caroline; Khreish, Fadi; Ezziddin, Samer
Abstract: An 85-year-old man with advanced metastatic castration-resistant prostate cancer and progression after 8 cycles of 177 Lu–prostate-specific membrane antigen (PSMA)–617 radioligand therapy (RLT) received 1 cycle of 161 Tb-PSMA RLT. This one administration of 6.5 GBq 161 Tb-PSMA-617 resulted in impressive partial remission with a PSA decline by 53.4% (from 474 to 221 ng/mL) and a concomitant decrease in tumor burden on PSMA PET/CT imaging. The presented case provides stunning initial evidence of the therapeutic potential of 161 Tb-PSMA RLT in metastatic castration-resistant prostate cancer, even in patients progressing after extensive 177 Lu-based RLT. 161 Tb-labeled PSMA ligands may thus offer a promising alternative to standard PSMA RLT.